Penerapan Metode Inside Outside Circle (IOC) dalam Meningkatkan Hasil Belajar IPA tentang Sifat-Sifat Benda dan Kegunaannya pada Peserta Didik Kelas III A SD Negeri Kasreman di Semester I Tahun Pelajaran 2018/2019 - Juprihadi, Juprihadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
This research is a Class Action Research (CAR) with the purpose to analyze theapplication of Inside Outside Circle (IOC) method in increasing the learning outcome ofnatural science about the object’s characteristics and usefulness on the students of Class III Athe Elementary School of Kasreman on the first Semester of the 2018/2019 year academic. Thesubjects of this research are the students of Class III A the Elementary School of Kasreman onthe first Semester of the 2018/2019 year academic as much as twenty four children; consist offifteen boys and nine girls. The data resources of this research are relating with learningactivities and learning outcomes. Techniques of collecting data of this research are non testtechnique and test technique. The instruments of collecting data of this research are the sheetsof observation and the camera application on the hand phone and also daily test. Technique ofanalyzing data of this research is comparative description. The procedure of this research is theKemmis and Mc Taggart’s spiral model that consist of two cycles; First Cycle and SecondCycle. Each cycle is consisting of two meetings. The results of this research are 1) theapplication of Inside Outside Circle (IOC) method in the learning of science about the object’scharacteristics and usefulness is a different task for each group, 2) the application of InsideOutside Circle (IOC) method in the learning of science about the object’s characteristics andusefulness is in a small group, consist of three-four members, 3) the applications of InsideOutside Circle (IOC) method in the learning of science about the object’s characteristics andusefulness are increasing the learning activities; actively in discussing, very actively inanswering the questions from the teacher and other students and very actively in asking to theteacher, 4) the applications of Inside Outside Circle (IOC) method in the learning outcomes ofscience about the object’s characteristics and usefulness are increasing the learning outcomes.The learning outcomes on the Early Condition are 60,41 for the average and 47,82% for thecompleteness. The learning outcomes on the First Cycle are 73,75 for the average and 73,91%for the completeness. The learning outcomes on the Second Cycle are 84,58 for the averageand 91,3% for the completeness.